2019
DOI: 10.1186/s40360-019-0326-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential role of dose and environment in initiating and intensifying neurotoxicity caused by MDMA in rats

Abstract: Background MDMA causes serotonin (5-HT) syndrome immediately after administration and serotonergic injury in a few days or weeks. However, a serotonin syndrome is not always followed by serotonergic injury, indicating different mechanisms responsible for two adverse effects. The goal of present study was to determine causes for two adverse events and further test that dose and environment have a differential role in initiating and intensifying MDMA neurotoxicity. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…3,4-Methylenedioxymethamphetamine Neurotoxicity. Several studies have investigated whether MDMA is neurotoxic on neurotransmitter systems (Schmidt, 1987;Gudelsky et al, 1994;Armstrong and Noguchi, 2004;Granado et al, 2011;Shokry et al, 2019) given that this compound is also used to induce dopaminergic toxicity in mouse models (Blesa and Przedborski, 2014). Catechols derived from MDMA metabolism appear to be responsible for the neurotoxic effects of MDMA given that direct intracerebroventricular administration of MDMA does not elicit 5-HT neurotoxicity (Green et al, 2003).…”
Section: B Acute Side Effects Encountered In Uncontrolled Settingsmentioning
confidence: 99%
“…3,4-Methylenedioxymethamphetamine Neurotoxicity. Several studies have investigated whether MDMA is neurotoxic on neurotransmitter systems (Schmidt, 1987;Gudelsky et al, 1994;Armstrong and Noguchi, 2004;Granado et al, 2011;Shokry et al, 2019) given that this compound is also used to induce dopaminergic toxicity in mouse models (Blesa and Przedborski, 2014). Catechols derived from MDMA metabolism appear to be responsible for the neurotoxic effects of MDMA given that direct intracerebroventricular administration of MDMA does not elicit 5-HT neurotoxicity (Green et al, 2003).…”
Section: B Acute Side Effects Encountered In Uncontrolled Settingsmentioning
confidence: 99%
“…It has been previously proposed that hyperthermia induced by amphetamine-related drugs may increase the formation of ROS and reactive nitrogen species (Chipana et al, 2008;Sharma and Ali, 2008;Shokry et al, 2019). However, other studies have demonstrated that MDMA may increase the levels of oxidative stress by mechanisms other than the induction of hyperthermia (Jayanthi et al, 1999;Peraile et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our and other laboratories have suggested that hyperthermia, which is a commonly observed noxious effect of MDMA (Green et al, 2003;Hall and Henry, 2006), may favor the neurotoxicity and/or glia activation induced by this amphetamine-related drug (Miller and O'Callaghan, 1995;Colado et al, 1998;Mechan et al, 2001;Touriño et al, 2010;Frau et al, 2013), with a mechanism that is thought to stem from increased production and release of reactive oxygen species (ROS) (Chipana et al, 2008;Sharma and Ali, 2008;Shokry et al, 2019). However, other authors have demonstrated that MDMA can induce the release of ROS and neurotoxicity in experimental animals by means of mechanisms that are independent of hyperthermia (Green et al, 2004).…”
Section: Introductionmentioning
confidence: 99%